Lakon Mintaraga ke Sang Indrakila Resi Kajian Alih Wahana (The Play of Mintaraga to Sang Indrakila Resi: Study of a Change from One Type of Art to Another) - Endah Budiarti (Institut Seni Indonesia Yogyakarta, 2020)
AbstractThe Play of Mintaraga to Sang Indrakila Resi: Study of a Change from One Type of Art to Another. This study aimed to trace the art transformation of the Mintaraga play to Sang Indrakila Resi. In other words, tracing the art transformation from play to written play. Sapardi Djoko Damono’s theory of art transformation is used as a framework for thinking in this study. Sapardi Djoko Damono’s theory states that art transformation is the change and transfer of “something” from one type of art to another. This study used descriptive qualitative method. The data collection and processing methods used in this study were note-taking, listening, sorting, and orthographic matching techniques. The method used in the data analysis stage was the literary method (library methods). The result of this study was a formula for transfer of art from play to written play. AbstrakTulisan ini bertujuan melacak alih wahana lakon Mintaraga ke Sang Indrakila Resi. Dengan kata lain melacak alih wahana dari lakon pertunjukan ke lakon tulis. Teori alih wahana Sapardi Djoko Damono dipakai sebagai kerangka berpikir dalam penelitian ini. Teori Sapardi Djoko Damono mengatakan bahwa alih wahana adalah pengubahan dan pemindahan “sesuatu” dari satu jenis wahana ke jenis wahana lain. Temuan yang dihasilkan ialah formula alih wahana dari lakon pertunjukan ke lakon tulis.